Publikasi Produk Hukum Daerah Kabupaten/Kota Kepada Masyarakat Melalui Official Web Provinsi Jambi - Windarto; Iskandar Zulkarnain; Syamsir (Jurnal Hukum Respublica, 2018)
The purpose of this study is to explain the efforts to publish district / city regional legal products to the public through the official web in Jambi Province, and to explain any obstacles in the publication of district / city regional legal products to the public through the official web in Jambi Province. This type of research is empirical juridical, which is conducting research on the publication of district / city legal products to the public through the official web in Jambi Province. The results of the research can be explained by the publication of regency / city regional legal products to the public through the Official Web in Jambi Province, which has not been implemented by all regencies / municipalities in the Province of Jambi, in terms of the number of regencies / cities, the number of regional legal publications published or the official JDIH Web. Constraints on the publication of district / city regional legal products to the public through the Official Web in Jambi Province, namely institutional constraints. OPD has the authority to publish regional legal products, human resources and lack of public awareness. In addition, there is also weak coordination between the legal department and the Office of Communication and Information. Related to this conclusion, the writer suggests that it is necessary to arrange a program for the number of regency / municipal legal products in Jambi Province which are still active since the birth of the regency / city. Regencies / cities must strengthen coordination between the legal department and the Office of Communication and Information in the publication of regional legal products, specifically in the arrangement of the number of regional legal products, increasing human resources and strengthening the budget. Cooperation between the Faculty of Law of the University of Jambi and the regencies / cities in Jambi Province is needed for the publication of regional legal products through the University of Jambi Faculty of Law website.